91.2k views
4 votes
The function h(x) = (x + 6)^8 can be expressed in the form f(g(x)) where f(x) = x ^ 8 and, g(x) is defined below g(x) =

1 Answer

2 votes

Answer:

g(x) = x + 6

Step-by-step explanation:

We know that


\begin{gathered} h(x)=(x+6)^8 \\ and \\ f(x)=x^8 \end{gathered}

If h(x) = f(g(x)), we need to make g(x) = x + 6 to get


\begin{gathered} f(g(x))=(g(x))^8 \\ f(g(x))=(x+6)^8 \end{gathered}

Therefore, the answer is g(x) = x + 6

User Socob
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.